Use of Mental Health Services for Patients Diagnosed with Major Depressive Disorders in Primary Care - González-Suñer, Laura (Int J Environ Res Public Health, 2021)
Major depressive disorder (MDD) is one of the most disabling diseases worldwide, generating high use of health services. Previous studies have shown that Mental Health Services (MHS) use is associated with patient and Family Physician (FP) factors. The aim of this study was to investigate MHS use in a naturalistic sample of MDD outpatients and the factors influencing use of services in specialized psychiatric care, to know the natural mental healthcare pathway. Non-randomized clinical trial including newly depressed Primary Care (PC) patients (n = 263) with a 12-month follow-up (from 2013 to 2015). Patient sociodemographic variables were assessed along with clinical variables (mental disorder diagnosis, severity of depression or anxiety, quality of life, disability, beliefs about illness and medication). FP (n = 53) variables were also evaluated. A multilevel logistic regression analysis was performed to assess factors associated with public or private MHS use. Subjects were clustered by FP. Having previously used MHS was associated with the use of MHS. The use of public MHS was associated with worse perception of quality of life. No other sociodemographic, clinical, nor FP variables were associated with the use of MHS. Patient self-perception is a factor that influences the use of services, in addition to having used them before. This is in line with Value-Based Healthcare, which propose to put the focus on the patient, who is the one who must define which health outcomes are relevant to him.